SENIOR TOURISM AND CHANCE FOR TOURISM BUSINESS PLAYERS - Farma Mangunsong (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Increasing the number of elderly people in the world creates an opportunity for the tourism business. To be in line with this, business players in the tourism sector have to cope with their social demographic factors such as age, gender, income, cultural values, and also promotion methods to promote senior tourism. The objective of this study is to describe the social demographic characteristics and needs of potential elderly people so that business players can utilize the phenomena and collected information as a benefit to promote tourism for elderly people or senior tourism. This study used SWOT analysis to identify strength, weakness, opportunity, and threat of senior tourism business as well as to formulate strategies for senior tourism. The literature review was conducted to collect information about elderly people having senior tourism. It is found that social demographic characteristics influence the needs and motivation of elderly people in senior tourism. Senior tourists from high-income levels need high quality of service, beautiful scenery, and privacy while those from middle-income levels prefer attractions and festivals. Senior tourists with “young at heart” prefer more challenging activities as well as younger and male senior tourists, while those with “old at heart” put higher concern on convenience and security as well as older and female tourists. Leisure, cultural values, and personal achievement motivate elderly people to have senior tourism. Leisure with family and parents motivates senior tourism in Asia but living away from materialistic life is more appropriate for western people. Creating several traveling packages to adapt to various characteristics of elderly people will enlarge the market for the tourism sector. Providing better facilities adopting physical need of elderly people make them confident to travel. Business players can use digital social media to promote senior tourism to elderly people as well as to current adult children since current old parents experience higher technological exposure rather than their previous counterparts.